(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The internet has become one of the most important necessities in the present world. Web technology is a collective name for technology primarily for the World Wide Web (WWW). The three core languages that form up the globe Wide Web are HTML, CSS and JavaScript. The present student management system helps in maintaining student records and the project management system is an industry-based software that is used to assign work to a group of people. The student management system only manages the student information and the project management system doesn’t allow a person to monitor the team and give instructions based on it. ProTrack incorporates both project management and student management software and brings an industrial workspace to the students. Here students can form teams with peer students to work on their innovative projects. ProTrack provides an environment where students could work - teachers could support. Hence improves the ability of the students to work as a team under supervision.